Power Imbalances in Society and AI: On the Need to Expand the Feminist Approach - Gengler, Eva; Wedel, Marco; Wudel, Alexandra; Laumer, Sven (Conceptualizing Digital Responsibility for the Information Age, 2025)
Recent advances in artificial intelligence have brought novel opportunities for businesses, societies, and individuals alike, yet they also raise complex questions on inequitable power distribution. We see contemporary AI systems, that reinforce power imbalances and disadvantage marginalized, underrepresented, and underprivileged people. Current approaches to advancing AI, such as ethical, fair, or trustworthy AI, have not included the effects of power in their considerations. As feminism has a long history of doing so, we introduce an intersectional and inclusive feminist approach to shape AI in a more equitable way. We approach this by building on recent information systems and interdisciplinary research as well as on evidence from expert interviews in focus groups, which we conducted in 2022 and 2023. Our study reveals that utilizing a feminist approach could be effective firstly, to shape AI systems and secondly, to change prevailing power structures in societal systems to become more equitabl
Keywords: Artificial intelligence; Power imbalances; Feminist philosophy of technology; Socio-technical-systems; Beyond AI ethics